Functional jelly candy of moringa leaves, ginger, and dragon fruit for pregnant women - Ratnawati, Ratnawati; Utami, Riana Pangestu; Novaria, Astri Ayu (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: To ensure sufficient iron intake while addressing nausea in pregnant women, innovative food products utilizing local ingredients are needed. The health benefits of Moringa leaves, ginger, and dragon have been well-documented; however, there is limited research on the combined effects of these ingredients in functional food formulations specifically designed for pregnant women.Objectives: This study aims to develop a jelly candy formulation combining moringa leaves, ginger, and dragon fruit as an alternative source of iron and anti-nausea remedy for pregnant women.Methods: This research employs an experimental design with a Completely Randomized Design, using jelly candy formulations from combinations of moringa, ginger, and dragon fruit. The research was conducted at Organoleptic Laboratory Health Polytechnic of East Kalimantan and Politani Laboratory from July to Augustus 2024. The study involves one factor: variations in moringa powder concentration, which are 0.5% (F1), 1% (F2), and 1.5% (F3), with three replications. The jelly candy formulations were subjected to 33 untrained panelist to hedonic testing for color, taste, aroma, and texture, followed by chemical characteristic testing. Data analysis was performed using one way ANOVA and post hoc Duncan Multiple Range Test.Results: The study results indicate that the three formulations showed a significant difference only in texture attributes (p = 0,033), while color, taste, and aroma remained at comparable levels. The formulation with the most preferred taste, aroma, and texture was F3, with a taste score of 3,5, aroma score of 3,,3, and texture score of 3,8. Meanwhile, the most preferred color attribute was observed in F1, with a score of 3,9. A significant difference was found among the three formulations in terms of moisture content (p = 0,030), ash content (p = 0,010), sucrose content (p = 0,000), and iron (Fe) content (p = 0,002).Conclusion: The F3 jelly candy can be used as an alternative snack providing both iron supplementation and anti-nausea benefits for pregnant women. It can be consumed in addition to iron tablets or other multivitamin.